2002
DOI: 10.1021/nl015705t
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Size Effects in Carbon Nanotube Intramolecular Junctions

Abstract: We calculated the effect of varying the length of a metal-semiconductor carbon nanotube junction on its electrical properties. Joining a metallic (5,5) tube to a semiconducting (10,0) tube leads to the creation of new states near the Fermi energy and produces a larger conductance gap (about 2 eV) than the band gap of the semiconducting segment (about 1 eV). The new states reflect the charge transfer from the (5,5) to the (10,0) segment. The larger conductance gap is due to the mismatch in the conducting states… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
44
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 19 publications
2
44
0
Order By: Relevance
“…The lowest-lying interface state, labeled I1, is mainly localized at the interface, spreading towards the armchair side. This behavior was also observed in the interface states of (12, 0)/(6, 6) SLs and (10, 0)/(5, 5) junctions [23,24]. However, the second interface state (labeled I2) spreads considerably from the interface into the zigzag part.…”
Section: Interface States In Achiral Carbon Nanotube Junctionsmentioning
confidence: 58%
“…The lowest-lying interface state, labeled I1, is mainly localized at the interface, spreading towards the armchair side. This behavior was also observed in the interface states of (12, 0)/(6, 6) SLs and (10, 0)/(5, 5) junctions [23,24]. However, the second interface state (labeled I2) spreads considerably from the interface into the zigzag part.…”
Section: Interface States In Achiral Carbon Nanotube Junctionsmentioning
confidence: 58%
“…Many works, both in theory [59][60][61][62][63] and in experiment, have been performed to clarify the real electrical properties of the SWNT/SWNT junctions. By simulation, Rochefort and Avouris reported that a (5,5)/(10,0) junction could exhibit a rectifying behavior for lengths as small as 4 nm, and introduce a conductance gap (about 2 eV) and new states near the Fermi energy.…”
Section: Electrical Propertiesmentioning
confidence: 99%
“…The new states reflected the charge transferring across the junction, which caused a very low conductance over a wide range of energies. [63] Experimentally, in 1999, Yao et al first reported electrical transport measurements on the SWNT/SWNT junctions. [9] Current-voltage (I-V) curves measured across an M-S junction (Fig.…”
Section: Electrical Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Electronic structure of such heterojunctions was addressed first in Ref. [6] by employing the extended Huckel model. Subsequently, similar calculations were performed within the framework of other models [7].…”
mentioning
confidence: 99%